2020
DOI: 10.1093/jb/mvaa044
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned medium of the osteosarcoma cell line U2OS induces hBMSCs to exhibit characteristics of carcinoma-associated fibroblasts via activation of IL-6/STAT3 signalling

Abstract: As a research hotspot in recent years, bone mesenchymal stem cells (BMSCs) play an important role in the process of a variety of human diseases, including cancers. However, in osteosarcoma, the role of BMSCs and their communication with tumour cells are not clear. In this study, we validated the communication of osteosarcoma (OS) cells with BMSCs. The results showed that the conditioned medium of osteosarcoma cell line U2OS (U2OS-CM) induces the carcinoma-associated fibroblasts (CAFs)-like transformation of BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…For example, some studies have reported that osteosarcoma cells can also trigger the migration and invasion of endothelial cells and facilitate angiogenesis after exposure to MSCs. 198,[206][207][208] In regard to the immune response, MSCs can effectively release anti-inflammatory factors and suppress proinflammatory factors to assist osteosarcoma cells in immune escape, which is induced by autocrine or paracrine EVs, especially exosomes. 209 An interesting study reported that MSCs can secrete EVs containing miRNAs/RNAs and proteins to suppress the proliferation and immune response of T lymphocytes.…”
Section: The Immune Microenvironment Of Osteosarcomamentioning
confidence: 99%
“…For example, some studies have reported that osteosarcoma cells can also trigger the migration and invasion of endothelial cells and facilitate angiogenesis after exposure to MSCs. 198,[206][207][208] In regard to the immune response, MSCs can effectively release anti-inflammatory factors and suppress proinflammatory factors to assist osteosarcoma cells in immune escape, which is induced by autocrine or paracrine EVs, especially exosomes. 209 An interesting study reported that MSCs can secrete EVs containing miRNAs/RNAs and proteins to suppress the proliferation and immune response of T lymphocytes.…”
Section: The Immune Microenvironment Of Osteosarcomamentioning
confidence: 99%
“…Carcinoma-associated fibroblasts (CAFs) are a crucial component of the TME, contributing to the initiation, progression, and metastasis of various types of cancer, such as colorectal and pancreatic [33] . The differentiation of BMSCs to CAFs is a multistep and complex biological process, which may involve epithelial-mesenchymal transition, a bone marrow-derived progenitor, cellular communication, and cytokines [34] .…”
Section: Promotion Of Os Growthmentioning
confidence: 99%
“…Therefore, the transformation of BMSCs recruited to the OS site into CAFs, and their subsequent cytokine-induced mesenchymal-to-amoeboid transition, are key to the increase in OS heterogeneity. A follow-up study exposed BMSCs transformed to CAFs can significantly accelerate the proliferation, migration, and invasion of OS cells [33] . An in-depth study disclosed that, remarkably, U2OS could significantly induce the over-expression of IL–6 and phosphorylation of the STAT3 protein in BMSCs.…”
Section: Promotion Of Os Growthmentioning
confidence: 99%
“…The knockdown of GPR68 or the inhibition of IL-6/STAT3 pathway in MSCs suppress in situ tumor growth and prolong lifespan after cancer grafting [39]. Recently, Lin et al, showed that treating BM-MSC with a conditioned medium from osteosarcoma cell line U2OS transforms MSCs to CAFs via increasing IL-6 expression and the phosphorylation of STAT3, which further promotes the proliferation, migration, and invasion of BM-MSCs [40]. In another in vitro study, Pietrovito et al showed that BM-MSCs have a strong tropism towards OS cells, with cytokines such as MCP-1, GRO-α, and TGF-β1 being crucial factors in BM-MSC chemotaxis.…”
Section: Transformation Of Mscs Into Carcinoma-associated Fibroblastsmentioning
confidence: 99%